2020
DOI: 10.1136/rapm-2020-101558
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of adding the IPACK block to a multimodal analgesia protocol for primary total knee arthroplasty

Abstract: Background and objectivesPeripheral nerve blocks have been integrated into most multimodal analgesia protocols for total knee arthroplasty (TKA). The adductor canal block (ACB) has gained popularity because of its quadriceps muscle sparing. Similarly, local anesthetic injection between the popliteal artery and the posterior capsule of the knee, IPACK block, has been described to provide analgesia to the posterior capsule of the knee with motor-sparing qualities. This prospective randomized controlled trial aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 15 publications
7
70
0
Order By: Relevance
“…The search strategy identified 2180 unique citations. After independent and duplicate screening by two authors (RSD and BL), eight RCTs 13,[25][26][27][28][29][30][31] were identified that fulfilled eligibility criteria. Collectively, these eight RCTs consisted of 777 patients (377 patients received the iPACK block; 400 patients in the control cohort received another modality of peripheral nerve blockade or PAI for knee analgesia).…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The search strategy identified 2180 unique citations. After independent and duplicate screening by two authors (RSD and BL), eight RCTs 13,[25][26][27][28][29][30][31] were identified that fulfilled eligibility criteria. Collectively, these eight RCTs consisted of 777 patients (377 patients received the iPACK block; 400 patients in the control cohort received another modality of peripheral nerve blockade or PAI for knee analgesia).…”
Section: Search Resultsmentioning
confidence: 99%
“…Bias assessment for all included studies is summarized in Figure 2. All eight RCTs 13,[25][26][27][28][29][30][31] generally demonstrated a low risk of bias in random sequence generation and allocation concealment, blinding of outcome assessment, incomplete outcome data, and selective reporting. In terms of blinding of participants, some RCTs 13,25,26 displayed a high risk for bias because although they blinded all surgeons, recovery room and floor nurses, research assistants, statisticians, and patients, it was impossible to blind the anesthesiologist performing the ultrasound-guided iPACK block who may have participated in the study.…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations